Social Networks and Health Among Older Adults in Lebanon: The Mediating Role of Support and Trust - Webster, Noah J. (J Gerontol B Psychol Sci Soc Sci, 2015)
OBJECTIVES. Despite a growing body of literature documenting the influence of social networks on health, less is known in other parts of the world. The current study investigates this link by clustering characteristics of network members nominated by older adults in Lebanon. We then identify the degree to which various types of people exist within the networks. This study further examines how network composition as measured by the proportion of each type (i.e., type proportions) is related to health; and the mediating role of positive support and trust in this process. METHOD. Data are from the Family Ties and Aging Study (2009). Respondents aged ≥60 were selected (N = 195) for analysis. RESULTS. Three types of people within the networks were identified: Geographically Distant Male Youth, Geographically Close/Emotionally Distant Family, and Close Family. Having more Geographically Distant Male Youth in one’s network was associated with health limitations, whereas more Close Family was associated with no health limitations. Positive support mediated the link between type proportions and health limitations, whereas trust mediated the link between type proportions and depressive symptoms. DISCUSSION. Results document links between the social networks and health of older adults in Lebanon within the context of ongoing demographic transitions.